Introducing dominant currency pricing in the ECB's global macroeconomic model - Georgios Georgiadis; Saskia Mösle (European Central Bank (ECB), 2019)
A large share of global trade being priced and invoiced primarily in US dollar rather than the exporter's or the importer's currency has important implications for the transmission of shocks. We introduce this "dominant currency pricing" (DCP) into ECB-Global, the ECB's macroeconomic model for the global economy. To our knowledge, this is the first attempt to incorporate DCP into a major global macroeconomic model used at central banks or international organisations. In ECB-Global, DCP affects in particular the role of expenditure-switching and the US dollar exchange rate for spillovers: In case of a shock in a non-US economy that alters the value of its currency multilaterally, expenditure-switching occurs only through imports; in case of a US shock that alters the value of the US dollar multilaterally, expenditure-switching occurs both in non-US economies' imports and - as these are imports of their trading partners - exports. Overall, under DCP the US dollar exchange rate is a major driver of global trade, even for transactions that do not involve the US. In order to illustrate the usefulness of ECB-Global and DCP for policy analysis, we explore the implications of the euro rivaling the US dollar as a second dominant currency in global trade. According to ECB-Global, in such a scenario the global spillovers from US shocks are smaller, while those from euro area shocks are amplified; domestic euro area monetary policy effectiveness is hardly affected by the euro becoming a second globally dominant currency in trade.
Keywords: F42; E52; C50; 330; Global macroeconomic modelling; dominant currency paradigm; spillovers